2007
DOI: 10.1111/j.1365-2427.2007.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and microhabitats of freshwater sponges (Spongillidae) in a Danubean floodplain in Austria

Abstract: 1. This study examined the abundance and distribution of freshwater sponges (Spongillidae) at 32 sites in a floodplain on the Danube within the 'Donau-Auen' National Park east of Vienna, Austria. Ranked from abundant to rare, the species inventory comprised Ephydatia fluviatilis, Spongilla lacustris, Ephydatia mü lleri, Eunapius fragilis and Trochospongilla horrida. 2. The presence of hard substratum was essential for the growth of sponges. Timber stands near the water and drifting dead wood increased the abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…Por el momento el estatus de conservación de este grupo no ha sido abordado y su conservación queda bajo la protección genérica de especies con las que la conviven como los peces y los anfibios (Manconi & Pronzato, 2008). Esta circunstancia ha propiciado un cierto olvido en cuanto a su estudio, y también una cierta tendencia a menospreciar cuantitativamente la importancia relativa en el funcionamiento de los ecosistemas acuáticos de estas especies filtradoras que pueden llegar a ocupar grandes superficies sumergidas (Dröscher & Waringer, 2007). Si bien, su capacidad tapizante de superficies sumergidas está sometida a la competencia por los lugares de arraigo para las quimeras con el resto de la comunidad epilítica; pudiendo estar la parte del ejemplar más directamente expuesta a la luz solar asociado con microbios y carecer de éstos en la parte más oculta (Fig.…”
Section: Discussionunclassified
“…Por el momento el estatus de conservación de este grupo no ha sido abordado y su conservación queda bajo la protección genérica de especies con las que la conviven como los peces y los anfibios (Manconi & Pronzato, 2008). Esta circunstancia ha propiciado un cierto olvido en cuanto a su estudio, y también una cierta tendencia a menospreciar cuantitativamente la importancia relativa en el funcionamiento de los ecosistemas acuáticos de estas especies filtradoras que pueden llegar a ocupar grandes superficies sumergidas (Dröscher & Waringer, 2007). Si bien, su capacidad tapizante de superficies sumergidas está sometida a la competencia por los lugares de arraigo para las quimeras con el resto de la comunidad epilítica; pudiendo estar la parte del ejemplar más directamente expuesta a la luz solar asociado con microbios y carecer de éstos en la parte más oculta (Fig.…”
Section: Discussionunclassified
“…Most studies on the distribution of the species (Harrison, 1974;Richelle-Maurer et al, 1994;Økland & Økland, 1996;Dröscher & Waringer, 2007) agree in attributing to E. fluviatilis a preference for alkaline waters characterized by high conductivity and hardness, with the availability of hard substrate representing one of the most critical factors limiting the presence of the species. In Lake Trasimeno, a statistical analysis revealed that E. fluviatilis selectively colonizes hard substrata (rocks, pebbles, concrete and artificial objects), whereas soft sediments are strictly avoided (Lancioni & Gaino, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Sponges generally are successful only after settling on hard substrates, such as plants, woody debris, mollusk shells, mineral substrates, and artificial substrates (Manconi and Pronzato, 2008). Within floodplain habitats of a large European river, five species of sponges segregated between slack and swift waters (up to 0.25 m/s), chemical constituents of water (e.g., amount of Si), substrate type (e.g., wood or mineral substrates), and frequency of connectivity to the river mainstem (Dröscher and Waringer, 2007). Within smaller streams of Cuba, Ephydatia facunda (Weltner, 1895) is associated with gravel and boulder substrates in shallow (10 to 40 cm) and flowing waters shaded by dense riparian vegetation (Manconi and Pronzato, 2005).…”
mentioning
confidence: 99%